Speculations on the True Holy Grail - Sorensen, Richard (Journal of Scientific Exploration, 2023)
The Holy Grail is generally thought of as the chalice that Jesus Christ used at the Last Supper, and which was also said to be used by Joseph of Arimathea to catch Christ’s blood when his side was pierced on the cross. Grail legends and lore have fascinated people since the Middle Ages when the literary concept was first popularized, and the Holy Grail has become one of the most enduring of all symbols. Fascination with the Grail has continued down through the centuries to the present, and includes works such as the 1989 movie Indiana Jones and the Last Crusade, with the ancient Templar Knight who utters the famous lines, “He chose poorly,” and, “You have chosen wisely!” The grail stories and romances were written starting in the twelfth century, more than one thousand years after Christ’s death, and were the most popular and compelling stories of their time. Many of them were associated with King Arthur, and virtually all of them were chivalric tales involving knights on some type of quest. However, in these grail stories, the identification of the grail as being the “Cup of Christ” was not always made. In the early stories, the grail was alternatively a serving dish, a stone, or something ethereal or spiritual that defies explanation, and the word “grail” can mean cup, chalice, dish, tureen, bowl, or platter.